Effect of canopy management on rooting pattern of Albizia procera and yield of crops under agrisilviculture system - Newaj, Ram; Dhyani, S.K.; Singh, Traloki; Kumar, Upendra; Neekher, Shikha (Indian Journal of Agroforestry, 2020)
The canopy management is a potential tool to minimize competition between trees and crops for above and below ground growth resources in agroforestry system. A field experiment was initiated during 2006-08 to find out the impact of canopy pruning of white siris [Albizia procera (Roxb.) Benth.] on root length density (RLD) of trees and crops under agrisilviculture system at National Research Centre for Agroforestry, Jhansi, Uttar Pradesh. The experiment consisted of three pruning regimes (70% canopy pruning, 50% canopy pruning and un-pruned trees). Blackgram [Vigna mungo (L.) Hepper]-mustard (Brassica juncia L. Czern. & Coss) crop sequence was taken as intercrop with tree. The experiment was conducted in randomized block design (RBD) with three replications. The findings revealed that plant population of crops was significantly reduced under un-pruned trees as compared to 70% canopy pruning. The growth and yield attributing characters of blackgram and mustard i.e. plant height, branches plant-1, pods plant-1 and siliquae plant-1 were significantly higher in 70% canopy pruning and 50% canopy pruning than un-pruned trees. In general, growth, yield attributes and yield of crops increased with increasing distances from tree base. The grain yield of both the crops under different pruning regimes was in order of 70% canopy pruning > 50% canopy pruning > un-pruned trees. The grain yield of blackgram at 0.5 m away from tree base was 2 to 5 times less than the yield achieved at 1.0, 2.0, 3.0 and 4.0 m away from tree base. The RLD adjacent the tree was higher and it reduced with increasing distances from tree base. Root concentration at 0-15 cm soil depth was comparatively higher than15-30cm soil depth. The RLD of crops-blackgram and mustard was higher under 70% canopy pruning and lower under 50% canopy pruning and un-pruned trees. In general, RLD of crops was lowest at adjacent tree base (0.5 m) and increased with increasing distances from tree base. The higher RLD in crops under 70% canopy pruning provide a strong evidence of more availability of growth resources that helps in higher plant population and better crop growth.